Penerapan Manajemen Mutu Pendidikan dalam Pelayanan Administrasi di SMK Pelayaran Katangka Makassar - M. Ahsan Agussalim (Attractive : Innovative Education Journal, 2024)
Quality management as a concept, its involvement is needed as an operational instrument in directing the administrative service process in a school. This study discusses the Application of Education Quality Management in Administrative Services at SMK Pelayaran Katangka Makassar. type of field research using a qualitative approach. Qualitative research does not use statistics, but through data collection, analysis, and then interpretation. It is usually related to social and human problems that are interdisciplinary, focusing on multimethod, naturalistic and interpretive (in data collection, paradigm, and interpretation). The data collection in this study was carried out directly at the Makassar Katangka Shipping Vocational School, as for the data collection techniques, namely: observation, interviews, and documentation. Data processing and analysis techniques are carried out by means of data reduction, data display, and verification. The results of this study show that education quality management then comes into a concept that offers a good direction to efforts to achieve the goals of a school. A good direction is to guide school management to obtain a quality standard that has a positive impact on society. Likewise, internally, the concept of education quality management is present to improve and fix things that are unequal internally so that it is able to maximize all services that are needed by school stakeholders.